2005
DOI: 10.1177/0021955x05053523
|View full text |Cite
|
Sign up to set email alerts
|

Discoloration in Fire-Retardant Flexible Polyurethane Foams

Abstract: The mechanism of discoloration (‘scorch’) of water-blown flame-retardant polyurethane (PU) foams has been studied. As UV spectroscopy showed, scorch is a kinetically controlled phenomenon, and it can occur either in flame-retardant or non-flame-retardant foams. Isolated isocyanate groups in the PU structure, which transform into aromatic amines, are mostly responsible for scorch. Some flame retardants tend to accelerate scorch, and it becomes visible during industrial foaming, especially in hot and humid weat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Mechanistic studies of the chemistry of scorch were performed at the University of Turin [98,99] under the sponsorship of Supresta. It was found that scorch is largely caused by the oxidation of aromatic amino groups which arise from the hydrolysis of isocyanate groups trapped in the PU network.…”
Section: Polyurethane (Pu) Foamsmentioning
confidence: 99%
“…Mechanistic studies of the chemistry of scorch were performed at the University of Turin [98,99] under the sponsorship of Supresta. It was found that scorch is largely caused by the oxidation of aromatic amino groups which arise from the hydrolysis of isocyanate groups trapped in the PU network.…”
Section: Polyurethane (Pu) Foamsmentioning
confidence: 99%
“…The incorporation of phosphorus is effective when its concentration is in the range of 1.0–1.5 wt % in the total formulation, and a further increase seems to produce no further benefit 74. However, scorch generation is the main problem in phosphorus‐modified fire‐retardant urethane foams 75–77. Ravey and Pearce50 incorporated phosphorus into a polyurethane foam formulation using H 3 PO4 (85%) in acetone, with the concentration ranging from 0.2 to 5.6%.…”
Section: Fire Retardancy Of Polyurethane Foamsmentioning
confidence: 99%
“…Catalysts play a vital role not only in the regulation and balance between the gelling and blowing reactions, but also in the optimization of the foam properties and the curing speed during the foam synthesis. Tertiary amines in combination with tin octoate are most widely used catalysts in the manufacture of polyurethane foams [18] [19].…”
Section: Resultsmentioning
confidence: 99%